Comorbidities are associated with poorer quality of life and functioning and worse symptoms in the 5 years following colorectal cancer surgery: Results from the ColoREctal Well-being (CREW) cohort study - Cummings, Amanda; Grimmett, Chloe; Calman, Lynn; Patel, Mubarak; Permyakova, Natalia Vadimovna; Winter, Jane; Corner, Jessica; Din, Amy; Fenlon, Deborah; Richardson, Alison; Smith, Peter W.; Foster, Claire (Wiley, 2018)
Objective: More people are living with the consequences of cancer and comorbidity. We describe frequencies of comorbidities in a colorectal cancer cohort and associations with health and wellbeing outcomes up to five years following surgery. Methods: Prospective cohort study of 872 colorectal cancer patients recruited 2010-2012 from 29 UK centres, awaiting curative intent surgery. Questionnaires administered at baseline (pre-surgery), 3, 9, 15, 24 months, and annually up to 5 years. Comorbidities (and whether they limit activities) were self-reported by participants from 3 months. The EORTC QLQ-C30 and QLQ-CR29 assessed global health/quality of life (QoL), symptoms and functioning. Longitudinal analyses investigated associations between comorbidities and health and wellbeing outcomes. Results: At baseline, the mean age of participants was 68 years, with 60% male and 65% colon cancer. 32% had one and 40% had >2 comorbidities. The most common comorbidities were high blood pressure (43%), arthritis/rheumatism (32%) and anxiety/depression (18%). Of those with comorbidities, 37% reported at least one that limited their daily activities. Reporting any limiting comorbidities was associated with poorer global health/QoL, worse symptoms and poorer functioning on all domains over 5 years’ follow-up. Controlling for the most common individual comorbidities, depression/anxiety had the greatest deleterious effect on outcomes. Conclusions: Clinical assessment should prioritise patient-reported comorbidities and whether these comorbidities limit daily activities, as important determinants of recovery of QoL, symptoms and functioning following colorectal cancer. Targeted interventions and support services, including multi-professional management and tailored assessment and follow-up, may aid recovery of health and wellbeing recovery in these individuals.